2008
DOI: 10.1016/j.bmc.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Lack of aquaporin-4 water transport inhibition by antiepileptics and arylsulfonamides

Abstract: Inhibitors of brain glial water channel aquaporin-4 (AQP4) are of potential clinical utility, as they are predicted to modulate brain edema, neuroexcitation and glial scarring. Recently, Huber et al. (Bioorgan. Med. Chem. 2007, 17:1270 2008, in press) reported that a series of arylsulfomamides, antiepileptics, and related small molecules strongly inhibited AQP4 water transport with IC50s down to 1 μM. We retested the compounds with greatest reported potencies, including acetylsulfanilamide, acetazolamide, 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 28 publications
(32 reference statements)
4
61
3
Order By: Relevance
“…In 2 different cell types, each with or without expression of orthogonally arrayed AQP4, separate cell-cell adhesion and dynamic light scattering assays demonstrated that AQP4 does not have any cell-cell adhesion property (31). Because in our 1.8-Å hAQP4 structure the C loop is not involved in the crystal packing, the lack of any helix in the C loop, therefore, supports the conclusion that AQP4 does not strongly drive adhesion, and that the 3 10 helix in the C loop observed in the rAQP4 structure may be induced by crystal contact.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…In 2 different cell types, each with or without expression of orthogonally arrayed AQP4, separate cell-cell adhesion and dynamic light scattering assays demonstrated that AQP4 does not have any cell-cell adhesion property (31). Because in our 1.8-Å hAQP4 structure the C loop is not involved in the crystal packing, the lack of any helix in the C loop, therefore, supports the conclusion that AQP4 does not strongly drive adhesion, and that the 3 10 helix in the C loop observed in the rAQP4 structure may be induced by crystal contact.…”
Section: Discussionsupporting
confidence: 60%
“…The rAQP4 2D crystal lattice has tetramers closer together (a ϭ 69.0 Å), and contains both in-plane and betweenplane contacts of the latticed tetramers. Based on the molecular contacts in the crystal, the interaction between the short 3 10 helices in the C loop was proposed to be a possible mechanism for AQP4-mediated cell-cell adhesion (Fig. S2b) (13).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 However, the effectiveness of acetazolamide and antiepileptics as AQP blockers has been disputed. 12 The bumetanide derivative AqB013 (Aq, aquaporin ligand; B, bumetanide scaffold) at 20 mM blocks AQP1 and AQP4 by a mechanism thought to involve physical occlusion of the intracellular water channel pore. 11 No direct pharmacologic agonist of AQPs has previously been described.…”
mentioning
confidence: 99%